(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Field studies were conducted during the 2013 and 2014 growing seasons in central Texas near Taylor (30.5326o N; 97.4548o W) to determine the effect of hybrid, row spacing, and plant populations on corn growth and yield. Two corn hybrids (BH 8844 and BH 8900) were compared at 53,000, 62,000, and 71,000 plants ha-1 planted one row on a single bed or twin rows (spaced approximately 20 cm apart) on a single bed. Plant counts were taken 4 to 6 wk after planting while ear height measurements were taken approximately four wk prior to corn harvest. Crop yield was determined by harvesting all eight rows of each plot with a combine. Weights were adjusted to 12% moisture. Experimental design was a factorial arrangement using a randomized complete block design with corn hybrid (2), row spacing (2), and seeding rates (3) as factors. Data were analyzed using PROC GLM with SAS (SAS Institute, Inc., Cary, NC) and treatment means separated by Fisher’s protected least significant difference test at P = 0.05. Plant height was not affected by plant populations or row spacing as only hybrid response was significant with BH 8900 being taller in both years. Row spacing affected ear height in one of two years with the twin row spacing having a taller ear placement in the dryer year. No differences were seen with ear placement with respect to plant populations. In the dry year, yield of BH 8844 decreased as plant populations increased; however, no differences were noted with BH 8900. In the wet year, the inverse was seen with increased yield with higher populations with both hybrids. The twin row system increased BH 8900 yield in 2013. In 2014, with BH 8844, the single row system outyielded twin row and no differences noted with BH 8900. The results were quite variable and this was due in part to rainfall events in the two years. Plant and ear height was influenced by hybrid while yield response was somewhat affected by population and row spacing. A hybrid x row width response was noted indicating that certain hybrids will respond to row spacing more than others.